Electroacupuncture Inhibits Ferroptosis Induced by Cerebral Ischemiareperfusion - Wang, Gui-Ling; Xu, Shu-Ying; Lv, He-Qun; Zhang, Chao; Peng, Yong-Jun (Current Neurovascular Research, 2023)
Background: Electroacupuncture (EA) treatment has been recommended by World Health Organization (WHO) for years on cerebral ischemia treatment, but the specific mechanism is still elusive. Studies have shown that EA can relieve brain damage after ischemic stroke by inhibiting programmed cell death (PCD), such as apoptosis, necroptosis, and autophagy. Ferroptosis, a unique form of cell death, has been highlighted recently and found to occur in I/R injury. We, therefore, investigated whether EA plays an essential role in relieving cerebral I/R injury via ferroptosis. Methods: The modified MCAO/R rats model was established and then divided into four groups with or without EA treatment. Neurological deficit score and TTC staining were used to evaluate the neurological deficit and infarct volume of each group. Transmission electron microscope (TEM) and immunofluorescence staining were applied for mitochondrial ultrastructure and ROS accumulation observation, respectively. The proteins and mRNA expression of ACSL4, TFR1, and GPX4 were assessed by western blot and qPCR to detect the progress of ferroptosis. Results: EA treatment improved neurological deficits and reduced infarct volume. Moreover, EA significantly relieved the mitochondrial morphological changes and inhibited ROS Production in MCAO rats. In terms of its mechanism, EA obviously decreased the ACSL4 and TFR1 expressions and promoted GPX4 levels in MCAO/R model rats. Conclusion: These findings indicate that EA might play an essential role in relieving cerebral I/R injury via ferroptosis.
Keywords: MCAO rats